Exploring Country-of-Origin Perceptions and Ethnocentrism: The Case of U.S. Dairy Marketing in China. Issue 2 (12th February 2020) - Xu, Xiaohan; Comello, Maria Leonora G.; Lee, Suman; Clancy, Richard
ABSTRACT: We examined variables relevant to food products marketing in foreign markets: perceptions of a product's country-of-origin (which may provide a "halo effect" if positive), and consumers' tendencies to favor local vs. imported goods for ideological reasons (consumer ethnocentrism). These were explored in the context of marketing research related to expanding U.S. dairy in China. An online survey of consumers (N = 505) in Beijing, Shanghai, and Guangzhou showed that ethnocentrism was below scale mid-point and did not vary across cities. Overall, higher purchase intention was associated with more favorable evaluations of the U.S., and with lower ethnocentrism, although there were some differences by region. Theoretical and practical implications are discussed.